Activity of rosemary (Rosmarinus officinalis-Family: Lamiaceae) essential oil compared to peracetic acid in Listeria monocytogenes biofilms - Dos Santos, Emanoelli Aparecida Rodrigues [UNESP]; Tadielo, Leonardo Ereno [UNESP]; Belle, Thiago Henrique; Schmiedt, Jhennifer Arruda; Dias, Victor Hugo Cortez; Orisio, Paulo Henrique Silva; Cerqueira-Cézar, Camila Koutsodontis [UNESP]; Pereira, Juliano Gonçalves [UNESP]; Barcellos, Vinicius Cunha; Bersot, Luciano Dos Santos (Universidade Estadual de Maringa, 2023)
The objective of this study was to evaluate the activity of Rosmarinus officinalis essential oil (EO) compared to peracetic acid (PA) regarding formation and elimination of Listeria monocytogenes biofilms on polystyrene surface. The minimum inhibitory concentration (MIC) was determined according to standard protocol. Isolates were inoculated according to MIC standards polystyrene plate wells, which were then incubated at 37°C/96 hours for evaluation of biofilm formation. Regarding the evaluation of biofilm elimination, the biofilms were treated under MIC for 10 minutes. The MIC obtained were 2.0 and 3.0 mg mL-1 for EO and 0,015% for PA. Therefore, the results showed a reduction in the formation of biofilm with the presence of EO and PA, EO being more efficient (p < 0.05). Both compounds had a good capacity of eliminating biofilms, however the EO reduced the biofilm formation when compared to PA, highlighting its potential as an antibacterial agent and antibiofilm.
Keywords: control methods; industrial surface; rosemary; sanitization